Locus Of Control in Cancer And Cardiac Patients: Comparison Across Gender And Socio-economic Status (Chittagong University Journal of Biological Sciences, 2024)
The objective of the study was to explore the locus of control in cancer and cardiac patients in comparison to gender and SES (socio- economic status). A total of 360 respondents constituted the sample of the present study. Modification of Rotter’s Internal-External Control of Personality Scale (Ara’s Bengali Adaptation 2006) was used for the collection of data. The sample was equally divided into three categories (cancer, cardiac, normal) on the basis of type of individuals (N=120 for each category). Again they were equally divided into male and female on the basis of gender (N=60 for each group).Each category was again equally subdivided into lower middle and upper middle on the basis of SES (N=30 for each group). Results analyzed through ANOVA revealed that the main effects for type of individuals, gender and SES were statistically significant. That is, Both cancer and cardiac patients were more externally controlled as compared to normal individuals, Females were more externally controlled as compared to males and lower middle SES individuals were more externally controlled as compared to upper middle SES individuals. Again the two way interactions between type of individuals & gender, and gender & SES were statistically significant.The Chittagong Univ. J. B. Sci.,Vol. 7(1 &2):131-149, 2012.